2020
DOI: 10.1016/j.adro.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Evaluation of PSMA PET-Delineated Dominant Intraprostatic Lesion Simultaneous Infield Boosts

Abstract: Prostate cancer is multifocal. However, there often exists a single dominant focus in the gland responsible for driving the biology of the disease. Dose escalation to the dominant lesion is a proposed strategy to increase tumor control. We applied radiobiological modeling to evaluate the dosimetric feasibility and benefit of dominant intraprostatic lesion simultaneous in-field boosts (DIL-SIB) to the gross tumor volume (GTV), defined using a novel molecular positron emission tomography (PET) probe (18F-DCFPyL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Autoplanning is a current hot topic of development to reduce interplanner variability while generally improving plan quality. 3 For PC-SBRT, the feasibility of autoplanning for even complex techniques as simultaneous integrated boost to the dominant intraprostatic lesion has been reported 20 , and as shown in Figure 2S Fig. 1 Box-and-whisker plots of the metrics computed from the 50 manual plans (left) and mCycle plans (right).…”
Section: Discussionmentioning
confidence: 96%
“…Autoplanning is a current hot topic of development to reduce interplanner variability while generally improving plan quality. 3 For PC-SBRT, the feasibility of autoplanning for even complex techniques as simultaneous integrated boost to the dominant intraprostatic lesion has been reported 20 , and as shown in Figure 2S Fig. 1 Box-and-whisker plots of the metrics computed from the 50 manual plans (left) and mCycle plans (right).…”
Section: Discussionmentioning
confidence: 96%
“…They found that the mean dose to the tumor tissue – defined as the pathological volume established from the 68 Ga-PSMA positive volumes – can be increased significantly without any significant increase in the mean dose to rectum and bladder. In 6 patients who underwent 18F-DCFPyL PET/CT, Goodman et al [37] likewise found that PSMA PET can be used as a novel approach to defining the gross tumor volumes for the purposes of dominant intraprostatic lesion simultaneous in-field boost (DIL-SIB) dose escalation. No data on the effect of PSMA PET on patient prognosis in this setting have become available as yet, however.…”
Section: Discussionmentioning
confidence: 99%
“…In case intraprostatic SUVmax is close to the applied SUVmax for manual scaling, adjustment of the range, for instance SUVmin-max 0–5, might be considered as an appropriate alternative. Our results suggest, that the use [ 18 F]PSMA-1007 for contouring of lesions for focal therapy planning is likely to be as effective as other tracers, who’s performance was evaluated in radiotherapy planning studies and showed promising results in terms of tumor control and normal tissue toxicities ( 14 , 32 ).…”
Section: Discussionmentioning
confidence: 86%